If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -12y = 8 Solving 9x + -12y = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12y' to each side of the equation. 9x + -12y + 12y = 8 + 12y Combine like terms: -12y + 12y = 0 9x + 0 = 8 + 12y 9x = 8 + 12y Divide each side by '9'. x = 0.8888888889 + 1.333333333y Simplifying x = 0.8888888889 + 1.333333333y
| 6(2c+10)=5(c+5) | | 4n^2-7=-7n | | 30/20=x/4 | | 5c+9=4z-1 | | 3+4(x-5)=34 | | 9(x+1)+4(x+1)=6x-6 | | -6+11=-5-2 | | x^7-6x^5+2x^4-5=0 | | 2p-3=11 | | 3+7n=1+6n | | ln^3x=5 | | 5k^2=6-k | | (x+1)+(y-2)=7 | | 4x+25=8x+37 | | 16-2w=5w+9 | | 8x=215-13x | | 65+7x+5x-5=180 | | 5x^3+2x^2-x=0 | | 4y=12x-5 | | 7p+14=p-4 | | 6n^2-8=-93 | | -132=-7d-4d | | 8+3e^3x=26 | | 25a^2+8=108 | | 3h+12h=18 | | -5+3m=2m+2 | | X/7=10/2 | | 70+x+80+x+40=180 | | 8+3e=26 | | n^2=6+n | | 0=-4u^2-31u-50 | | X(5-x)=8-(x+3) |